Pelatihan Akuntansi Berbasis Sistem Informasi Akuntansi Pada SMK Cahaya Surya - Kayetanus Aldy Pratama; Ferdy Yunanto; Duwi Riningsih; Mukti Prasaja (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
The subject of accounting information systems is still one of the subjects that are still incorporated in the subject of information systems, not a stand-alone subject. This in-depth knowledge of accounting lessons has many benefits in everyday life. Thus, it is very necessary to have an addition given to vocational students. The objectives of the activity are as follows: (1) Participants are expected to understand the process of Accounting Information System and basic accounting records and an increase in understanding, (2) Participants can understand the benefits of Accounting in daily life and (3) Participants know the accounting profession which includes the field of accounting. who are very broad in the world of work so that it becomes an inspiration if they continue to college. The methods used in carrying out the activities, namely: Giving handouts for reading materials for participants related to the topic of socialization about simple accounting in small companies. Conducting socialization/lectures in the field of accounting, discussions, and working on cases.